Comparative Genome Analysis of 19 Trueperella pyogenes Strains Originating from Different Animal Species Reveal a Genetically Diverse Open Pan-Genome - Zoozeal Thakur; Rajesh Kumar Vaid; Taruna Anand; Bhupendra Nath Tripathi (Antibiotics, 2022)
Trueperella pyogenes is a Gram-positive opportunistic pathogen that causes severe cases of mastitis, metritis, and pneumonia in a wide range of animals, resulting in significant economic losses. Although little is known about the virulence factors involved in the disease pathogenesis, a comprehensive comparative genome analysis of T. pyogenes genomes has not been performed till date. Hence, present investigation was carried out to characterize and compare 19 T. pyogenes genomes originating in different geographical origins including the draftgenome of the first Indian origin strain T. pyogenes Bu5. Additionally, candidate virulence determinants that could be crucial for their pathogenesis were also detected and analyzed by using various bioinformatics tools. The pan-genome calculations revealed an open pan-genome of T. pyogenes. In addition, an inventory of virulence related genes, 190 genomic islands, 31 prophage sequences, and 40 antibiotic resistance genes that could play a significant role in organism’s pathogenicity were detected. The core-genome based phylogeny of T. pyogenes demonstrates a polyphyletic, host-associated group with a high degree of genomic diversity. The identified core-genome can be further used for screening of drug and vaccine targets. The investigation has provided unique insights into pan-genome, virulome, mobiliome, and resistome of T. pyogenes genomes and laid the foundation for future investigations.